Physicochemical aspects of food engineering and processing - Devahastin, Sakamon , 1974- (Contemporary food engineering, 2011)
Physical and chemical interactions between various constituents resulting from processing operations often lead to physical, sensory, and nutritional changes in foods. Combining important information on processing and food quality, Physicochemical Aspects of Food Engineering and Processing describes the effects of various processing technologies on quality changes of different major foods in an integrative manner